Starting from the Beginning: On Building a School and Community-Based System Supporting the Gifted - David, Hanna (Richtmann Publishing, 2012)
Distinguished Ladies and GentlemenI feel honoured and privileged to be invited to deliver the 2011 Raphael Nosike Lecture courtesy of theRaphael Nosike Foundation(RNF) and African Association for Teaching and Learning(AATL).